Street Art: art and activism in Galicia. - Arévalo Iglesias, Lorena (Historia y Comunicación Social, 2014)
This paper aims to make an approach to the figure of the major artists of the current Galician Street Art, through formal analysis of his works and the linking of them with the social context in which they develop, to identify the main lines of his speech, considering the most critical aspect of this social and artistic discipline, whose study today deserves a separate chapter in books and art history courses or communication.